Cavernous Malformations of the Hypothalamus: A Single-institutional Series of 12 Cases and Review of the Literature. (16th November 2020) - Khahera, Anadjeet S; Li, Yiping; Steinberg, Gary K
Abstract: INTRODUCTION: There remains a paucity of literature on hypothalamic cavernous malformations (HCMs). METHODS: A prospectively managed database was retrospectively reviewed for patients diagnosed with HCM and treated surgically between 1987–2019. A PRIMSA-guideline systematic review of HCM in the literature was performed. RESULTS: Our cohort study consists of 12 patients with radiographically confirmed HCM treated with microsurgery by the senior author (GKS). We also identified an additional 16 surgically or conservatively managed patients from the literature and analyzed the data of all 28 patients (54% male, mean age 41+17 yrs (range 10 - 68). Patients harboring HCMs most commonly presented with headache (16/28, 57%), short-term memory impairment (10/28, 36%), and gait disturbance (9/28, 32%). Radiographically lesions most commonly involved the mammillary region (19/23, 82%), the tuberal/infundibulum region (13/23, 57%), and pre-optic/lamina terminalis region (11/23, 48%) with a mean diameter of 2.5+1.4 cm (range 0.8 - 7) at presentation. Acute hemorrhage was identified in 92% (24/26) of patients upon presentation with 85% (22/26) intraparenchymal and 31% (8/26) intraventricular. Of 24 patients who were managed surgically, gross total resection (GTR) was achieved in 83% (20/24) cases. There were no reports of perioperative infarct or mortality. With a mean follow-up period of 41 months (range 0.75 - 309 m), 73% (19/26) of patients experienced functional improvement, while 12% (3/26) had no change, and 15% (4/26) suffered from increased disability. In our cohort of 12 patients, 92% (11/12) continued to report symptoms at last follow-up (mean 4.9 yrs, range 0.2-25.7 yrs). However, there was a significant improvement in mRS noted after surgery (1.8 vs 3.3, P  = .01) and a trend towards improvement in GOSE (5.9 vs 4.8, p = 0.1). CONCLUSION: Hemorrhage from HCMs can cause symptomatic mass effect on adjacent eloquent structures. While patients are unlikely to be deficit-free following surgery, GTR allows for functional improvement and reduces recurrent hemorrhage rates. Microsurgery remains a viable option for hemorrhagic HCMs in experienced hands.